Pengaruh Faktor Fundamental Pada Nilai Perusahaan Manufaktur Sektor Basic Industry And Chemical Di Bursa Efek Indonesa - novalia, rosnita; aljufri, aljufri (Komunitas Manajemen Kompetitif, 2016)
This study aims to determine the influence of fundamental factors (EPS, DER, CR, TATO and size of the Company) on the value of the manufacturing company Basic Industry and Chemicals sector in Indonesia Stock Exchange 2011-2014 period. The population in this study are all companies Manufacturing Basic Industry and Chemicals sectors listed on the Stock Exchange the period 2011 to 2014, amounting to 63 companies While the sample was determined by purposive sampling method in order to obtain as many as 29 companies sampled. The analytical method used is multiple linear regression analysis with SPSS 17.00. Before the data were analyzed, performed classical assumption of the data. Statistical tests showed that (1) Taken together variable EPS, DER, CR, TATO, and company size effect on firm value (PBV) (2) Earning Per Share (EPS) effect on firm value (3) Debt to Equity ratio (DER) effect on firm value (4) Current ratio (CR) effect on the value of the company (5) Total Asset Turn Over (TATO) effect on the value of the company (6) the size effect on the company's corporate value. Keywords: Fundamentals, Earnings Per Share, Debt to Equity Ratio, Current Ratio, Total Asset Turn Over, Company Size, Price to Book Value, Value Company